A Case Study: How Social Media Advertisement Influences Consumer Behavior Toward a Fast-Food Restaurant - Lok, Yee Huei; Jian, Oh Zi; Chaudhary, Manoj Kumar; Khairul Azhar, Nurin Amni Bt; Azizi, Nurin Zahirah Bt; Azman, Nursyazana Afiqah Bt; Hassan, Nurul Husna Bt; Rohaan, Mohd; Kumari, Nidhi; Kee, Daisy Mui Hung (AIBPM Publisher, 2024)
Social media has become an increasingly important platform for shaping consumer behavior towards brands. Subsequently, social media is widely utilized and favored in most nations. This study examines the role of social media in shaping consumer behavior towards McDonald's, and how McDonald's leverages social media to enhance its brand image. A mixed-methods approach will be used, consisting of a survey of social media users and an analysis of McDonald's social media presence. The survey will explore how social media influences consumer behavior towards McDonald's, including how users engage with McDonald's social media accounts, the impact of user-generated content on their perceptions of the brand, and the role of social media in shaping their decision to visit McDonald's. The analysis of McDonald's social media presence will examine the types of content that the company shares, the engagement levels of its followers, and the impact of its social media campaigns on its brand image. The findings of this study will provide insights into how McDonald's can optimize its social media strategy to enhance its brand image and attract and retain customers